A Reliable Approach for Assessing Size-Dependent Effects of Silica Nanoparticles on Cellular Internalization Behavior and Cytotoxic Mechanisms [Corrigendum] - Kim W (Dove Medical Press, 2020)
Kim W, Kim WK, Lee K, et al. Int J Nanomedicine.  2019;14:7375– 7387. The authors have advised the affiliation list on page 7375 is incorrect. The correct author list and affiliations are as follows. Wooil Kim 1,2,*Won Kon Kim 1,*Kyungmin Lee 1Min Jeong Son 1Minjeong Kwak 3Won Seok Chang 4Jeong-Ki Min 1Nam Woong Song 3Jangwook Lee 1Kwang-Hee Bae 1 1Division of Biomedical Research, Korea Research Institute of Bioscience and Biotechnology (KRIBB), Daejeon 34141, Republic of Korea; 2Department of Biomolecular Science, KRIBB School of Bioscience, Korea University of Science and Technology (UST), Daejeon 34113, Republic of Korea; 3Center for Nano-Bio Measurement, Korea Research Institute of Standards and Science (KRISS), Daejeon 34113, Republic of Korea; 4Department of Nanoprocess, Korea Institute of Machinery & Materials (KIMM), Daejeon 34103, Republic of Korea  *These authors contributed equally to this work The authors apologize for this error. Read the original article